A Novel Route to Glass Fiber-Reinforced Epoxy Matrix Composites: Visible Light Activated Radical Induced Cationic Frontal Polymerization - Kurtulus, Cenk; Ciftci, Mustafa; Tasdelen, Mehmet Atilla (Wiley-V C H Verlag Gmbh, 2025)
In the current study, a novel radical-induced cationic frontal polymerization (RICFP) concept capable of rapid curing at room temperature via visible light irradiation is represented. Initially, the optimal formulation, which can be most effectively cured with visible light irradiation, is determined based on thickness, hardness, curing speed, and mechanical properties using FT-IR, DSC, TGA, and flexural test methods. Subsequently, the viability of the method is illustrated by fabricating glass fiber-reinforced composites through the hand lay-up technique, employing the optimized formulation and glass fibers in various forms (chopped strand mat and biaxial). Mechanical properties of the obtained composites, including bending, tensile, and shear tests, are carried out according to relevant international standards and compared with reference composites thermally cured with amine-based hardener by conventional method. A novel visible light curable epoxy resin for glass fiber-reinforced composites is developed, combining industrial-grade epoxy resin with a photoinitiator, photosensitizer, reactive solvent, and thermal initiator. Optimal formulation is identified by evaluating thickness, hardness, curing speed, and mechanical properties. The composites produced show mechanical properties comparable to thermally cured ones. image
Keywords: composites; epoxides; glass fibers; photoinitiator; photopolymerization